Pengaruh Profitabilitas, Leverage dan Komite Audit pada Tax Avoidance - Antari, Ni Wayan Desi; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2020)
The research aims to obtain empirical evidence regarding the effect of profitability, leverage, and audit committee on tax avoidance. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The total population of 42 companies using the method of determining the sample is the method of non-probability sampling, especially purposive sampling so as to obtain a total sample of 168. Hypothesis testing is done by using multiple linear regression analysis techniques. The results showed the profitability and audit committee variable had no effect on tax avoidance. The leverage variable shows a significant positive effect on tax avoidance. Keywords: Profitability; leverage; Audit Committee; CETR.